Imperial America (1914)
This publication presents the topic of finance and their respective administration that has developed in the U.S. either Democrat or Republican. Only since the beginning of this century, Americans have realized the great business opportunities that have occurred in Central and South America. / Abstract. Esta publicación expone el tema de las finanzas y su respectiva administración que se ha desarrollado en el estadounidense ya sea demócrata o republicano. Sólo desde el comienzo de este siglo se han dado cuenta los estadounidenses de las grandes posibilidades comerciales que se han dado en América Central y América del Sur.